Ilustração digital para iniciantes: desenvolvimento de manual didático para os estudantes de Design da UFAM - Souza, Ana Paula Machado de (Brasil, 2023)
This project aimed to develop a digital illustration manual for beginners, aimed at Design students at the Federal University of Amazonas (UFAM). The research and preparation of the manual were based on theoretical references on Digital Illustration, Editorial Design and Educational Design, to ensure the quality and effectiveness of the material produced. In addition, an opinion survey was conducted with the target audience to identify the most relevant and useful content and approaches for beginners in digital illustration. An analysis of similar works, such as digital illustration books by professional artists and specialized publishers, was also conducted to identify best practices and references in the field of digital illustration, ensuring the inclusion of relevant subjects and effective tutorials in the manual. After preparing the manual, a practical test was conducted with the students, in which they were invited to follow the tutorials and reproduce the drawings using a digitizing table. This test made it possible to assess the effectiveness of the manual and identify improvements and necessary adjustments. The results showed that the manual performed well in terms of teaching and guidance, but areas were identified that require adjustments and improvements to further enhance its effectiveness.